دراسة تأثير بعض العوامل التكنولوجية والفيزيائية على المساحة الفعلية لسطوح تماس الوصلات التداخلية الاسطوانية - بدور, جهاد (Latakia University Journal -Engineering Sciences Series, 2019)
في الوصلات التداخلية يتعلق ثبات الوصلة بمساحة التماس الفعلية للسطوح المقترنة لعناصر الوصلة، لذلك تمّ في هذا البحث دراسة المساحة الفعلية لتماس السطوح الاسطوانية، نمذجة العلاقات المحددة لها وتحليل العوامل المختلفة المؤثرة عليها (القساوة وطريقة التصنيع وبارامترات خشونة السطوح المتماسة)، ونتيجة ذلك تبين أن زيادة قساوة اللدونة في منطقة التماس تؤدي الى تقلص مساحة التماس الفعلية النسبية، بزيادة دقة تشغيل السطح يزداد مقدار مساحة التماس الفعلية النسبية، وبزيادة القطر الاسمي (d) لسطوح الاقتران تنخفض مساحة التماس الفعلية النسبية. In a valid tightness the steady coupled related into the actual area of contact of coupled surfaces which connected with coupled elements, so in this paper study the actual area of cylindered surfaces contacts and modeling the definite equations of the same, also has been analyzed the effected different coefficients such as ( hardness, manufacturing method and the parameters of rough contact surfaces ), and as a result of the same we can say that the increasing of the hardness plastic at the contact area leading into shrinking of the actual area contacts relatively, by increasing the precisely of manufacturing the surface, the actual area contacts relatively are increasing, and by increasing the nominal diameter ( d ) for contact surfaces, the actual area contacts relatively decreasing.